Multi-dimensional Studies on Thermotolerant Phosphate Solubilizing Bacteria Isolated from Rock Phosphate Mines for Bioactivation of Rock Phosphate. Issue 1 (3rd January 2023) - Yadav, Hemendra; Karkho, Richard; Mathur, Sujata
Abstract: We conducted multi-parametric studies on thermotolerant phosphate solubilizing bacteria useful in bioactivation of rock phosphate. Selected two different thermotolerant phosphate solubilizing cultures. Statistical optimization found pH, ammonium sulfate and EDTA concentration to be the significant variables for high phosphate solubilization by Bacillus sp. BISR-HY63. Alkaline phosphatase production by Brevibacillus sp. BISR-HY07 was increased from 1400 unitsL −1 to 3000 unitsL −1 . Partial purification of alkaline phosphatase performed by size exclusion and anion-exchange chromatography and the enzyme purified by 76 folds. Organic compost prepared and inoculated with alkaline phosphatase producing bacterium BISR-HY07 for increasing it's efficacy. Soluble P decreased from 9.5 mgKg −1 to 4.1 mgKg −1 and available P increased from 200 mgKg −1 to 1000 mgKg −1 after incubation of 50 days. When cultures used as bioinoculants, total P content absorbed by the plants inoculated by Brevibacillus sp. BISR-HY07 along with rock phosphate was highest and significantly higher at 9.3 gkg −1 . Shoot length of plants treated by rock phosphate and Brevibacillus sp. BISR-HY07 found to be highest and significantly higher at 31.5 cm. Root length, shoot biomass and root biomass of plants treated by rock phosphate and Bacillus sp. BISR-HY63 was highest but not significantly high at 10.3 cm, 0.73 g and 0.34 g respectively.